Ambient temperature NO oxidation over Cr-based amorphous mixed oxide catalysts: effects from the second oxide components. Issue 11 (15th May 2017) - Wang, Aiyong; Lin, Bo; Zhang, Hanlei; Engelhard, Mark H.; Guo, Yanglong; Lu, Guanzhong; Peden, Charles H. F.; Gao, Feng
Abstract : Three series of Cr-based mixed oxides (Cr–Co, Cr–Fe, and Cr–Ni oxides) with high specific surface areas and amorphous textures were synthesized using a novel sol–gel method. Abstract : Three series of Cr-based mixed oxides (Cr–Co, Cr–Fe, and Cr–Ni oxides) with high specific surface areas and amorphous textures were synthesized using a novel sol–gel method. These mixed oxides, in comparison to their pure metal oxide (CrO x, Co3 O4, FeO x and NiO) counterparts, display enhanced performance for catalytic oxidation of low-concentration NO at room temperature. The best performing catalysts achieve 100% NO conversion for ∼30 h of operation at a high space velocity of 45 000 ml g −1 h −1 . The amorphous structure was found to be critical for these catalysts to maintain high activity and durability. Control of the Cr/M (M = Co, Fe and Ni) molar ratio, nitrate precursor decomposition temperature and catalyst calcination temperature was key to the synthesis of these highly active catalysts.